The Influence of Leadership Style, Organizational Culture, and Job Satisfaction on Employee Performance Department of Education and Culture of Yapen Islands - Edison Musa Kayoi; Bonifasia Elita Bharanti; Sri Listyarini (Britain International for Academic Research (BIAR) Publisher, 2021)
The Department of Education and Culture of the Yapen Islands Regency as an extension of the local government in dealing with education has attempted to provide maximum public services. However, in its implementation, there are several obstacles, including not optimal services provided due to less-than-optimal employee performance. The objective of the study is to analyze the influence of leadership style, organizational culture, and job satisfaction on the performance of the employees of the Department of Education and Culture of the Yapen Islands Regency. Collecting data used a questionnaire. The research sample was calculated using the Slovin formula and obtained a total sample of 60 employees of the Department of Education and Culture of the Yapen Islands Regency. The data were tested with research instrument tests, classical assumption tests, and multiple linear regression tests using SPSS software version 25. The results showed that 1) leadership style had a positive and significant effect on employee performance, 2) organizational culture had a positive and significant effect on the performance of employees, 3) job satisfaction has no effect on employee performance